RESPON PEMUDA ASAL PULAU MAKEAN TERHADAP PANDEMI COVID-19 - Safrudin Amin; Dewi Apriani Aco; Zulkifli Zulkifli (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2023)
Many studies on the Covid-19 pandemic have explored various socio-cultural aspects related to this pandemic. Choosing a locus on Makean Island, this article focused on the responses of young villagers in Makean to the Covid-19 pandemic. The concept of response used in this article refers to the perspectives of environmental anthropology and psychological anthropology, namely the human response to external stimuli. In this context of study, we examined the responses of Makean Island youths to external stimuli, namely the COVID-19 pandemic and policies related to the pandemic. Using a combination of quantitative survey and qualitative ethnographic procedures, this study found several forms of responses to the COVID-19 pandemic. The responses we found were mainly in the area of ??seeking information about this pandemic: the level of trust in the existence of Covid-19, the perception of the risk of contracting Covid for both oneself and community, and the responses to pandemic mitigation policies, especially related to Covid-19 vaccinations. Another important finding is that although many Makean youths consider Covid-19 as dangerous, and they are at risk of contracting it, most of them do not view vaccination as the best preventive measure and therefore plan to take other preventive measures. This can be interpreted as a form of soft resistance to government policies that require all citizens to get vaccinated against Covid-19.